Analisis pengaruh fraud pentagon terhadap fraudulent financial reporting pada perusahaan subsektor consumer goods - Yuha Nadhirah Qintharah; Clarissa Ilmi Riyanti (Akuntansi dan Teknologi Informasi, 2023)
The study aims to examine elements of the pentagon's fraud theory that can influence the occurrence of fraudulent financial reporting. The pressure variable is proxied by financial targets; the opportunity is proxied by the ineffectiveness of supervision; the rationalization is proxied with auditor turnover; the competency is proxied by the change of the board of directors, and the arrogance is proxied by the frequency of the appearance of the CEO image. The population used in this study is manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The results of the study showed that financial targets had a significant negative effect on fraudulent financial reporting. Ineffectiveness of supervision, change of auditors, and changes of the board of directors did not affect fraudulent financial reporting, and the frequency of the appearance of the CEO image had a positive effect on fraudulent financial reporting.